2008
DOI: 10.1097/ccm.0b013e3181544248
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of propofol and lorazepam for critically ill patients undergoing mechanical ventilation*

Abstract: Objective-The economic implications of sedative choice in the management of patients receiving mechanical ventilation are unclear because of differences in costs and clinical outcomes associated with specific sedatives. Therefore, we aimed to determine the cost-effectiveness of the most commonly used sedatives prescribed for mechanically ventilated critically ill patients.Design, Setting, and Patients-Adopting the perspective of a hospital, we developed a probabilistic decision model to determine if continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 32 publications
0
23
0
1
Order By: Relevance
“…For example, although both propofol and dexmedetomidine have acquisition costs far higher than that of the benzodiazepines, recent pharmacoeconomic analyses have demonstrated that propofol and dexmedetomidine therapy is actually cheaper when each is compared with benzodiazepine therapy [39 ,40]. In fact, one recent cost-effectiveness analysis demonstrated that propofol dominated scheduled intermittent lorazepam in 91% of simulations and, on average, was $6378 less costly per patient [39 ]. In the MENDS trial, despite the higher acquisition cost of dexmedetomidine compared to lorazepam, the overall pharmacy, respiratory, ICU, and hospital costs were approximately equal between groups [7 ].…”
Section: Pharmacoeconomics Of Oversedationmentioning
confidence: 95%
“…For example, although both propofol and dexmedetomidine have acquisition costs far higher than that of the benzodiazepines, recent pharmacoeconomic analyses have demonstrated that propofol and dexmedetomidine therapy is actually cheaper when each is compared with benzodiazepine therapy [39 ,40]. In fact, one recent cost-effectiveness analysis demonstrated that propofol dominated scheduled intermittent lorazepam in 91% of simulations and, on average, was $6378 less costly per patient [39 ]. In the MENDS trial, despite the higher acquisition cost of dexmedetomidine compared to lorazepam, the overall pharmacy, respiratory, ICU, and hospital costs were approximately equal between groups [7 ].…”
Section: Pharmacoeconomics Of Oversedationmentioning
confidence: 95%
“…When compared with benzodiazepines, propofol has been shown to increase duration at target arousal level, reduce cost per patient, and decrease time spent on mechanical ventilation 6062,68. A meta-analysis comparing propofol to alternate sedation regimens for medium to long-term sedation demonstrated a decreased ICU length of stay that was significant when compared with the long-acting benzodiazepines (diazepam, lorazepam) but not when compared with the shorter- acting midazolam 69.…”
Section: Sedationmentioning
confidence: 99%
“…In a study by Dasta et al [38 ], a comparison of dexmedetomidine to propofol or remifentanil may also have been informative, as both propofol and remifentanil are rapidly cleared and may shorten duration of mechanical ventilation, and both are less costly than dexmedetomidine [44,45].…”
Section: Challenges and Pitfalls For Randomized Controlled Trials Witmentioning
confidence: 97%